2013
DOI: 10.1016/j.pep.2013.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Optimized protocol for expression and purification of membrane-bound PglB, a bacterial oligosaccharyl transferase

Abstract: Asparagine-linked glycosylation (NLG) plays a significant role in a diverse range of cellular processes, including protein signaling and trafficking, the immunologic response, and immune system evasion by pathogens. A major impediment to NLG-related research is an incomplete understanding of the central enzyme in the biosynthetic pathway, the oligosaccharyl transferase (OTase). Characterization of the OTase is critical for developing ways to inhibit, engineer, and otherwise manipulate the enzyme for research a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…Significant advances in defining OST structures using PglB and AglB have recently been reported, including the use of a protocol designed to optimize the expression and purification of active C. jejuni PglB in milligram amounts from E. coli (202); crystallography studies from the Kohda group on AglB from P. furiosus and A. fulgidus (30,185,203,204), including the first full-length archaeal OST (205); and solution of the X-ray structure of full-length Campylobacter lari PglB in complex with an acceptor peptide (195). The latter study showed that when bound with peptide, PglB forms two cavities on opposite sides of the protein.…”
Section: Aglb Structurementioning
confidence: 99%
“…Significant advances in defining OST structures using PglB and AglB have recently been reported, including the use of a protocol designed to optimize the expression and purification of active C. jejuni PglB in milligram amounts from E. coli (202); crystallography studies from the Kohda group on AglB from P. furiosus and A. fulgidus (30,185,203,204), including the first full-length archaeal OST (205); and solution of the X-ray structure of full-length Campylobacter lari PglB in complex with an acceptor peptide (195). The latter study showed that when bound with peptide, PglB forms two cavities on opposite sides of the protein.…”
Section: Aglb Structurementioning
confidence: 99%
“…In Vitro Glycosylation Assay-Und-PP-diNAcBac-[ 3 H]-GalNAc (36) and purified PglB were prepared as previously reported (72). Peptide substrate, Ac-HHHHHHYGSGSD-FNVS-CONH 2 (Ͼ96% purity) was purchased from Boston Open Labs (Cambridge, MA).…”
Section: In Silico Analysis Of N-linked Glycosylation Consensusmentioning
confidence: 99%
“…It is notable that PglB has been produced in vivo in E. coli and extracted with detergents (such as Triton X-100) while retaining activity. We hypothesize that in vivo, E. coli phospholipids support proper folding PglB, and remain associated with the enzyme through purification and detergent extraction, allowing the enzyme to remain in active conformation (Guarino & DeLisa, 2012;Jaffee & Imperiali, 2013). Ultimately, existing literature suggests that preferred membrane mimics vary between classes of membrane proteins and particular applications.…”
Section: Discussionmentioning
confidence: 99%
“…For example, membrane mimics such as micelles, liposomes, and nanodiscs have been used to synthesize membrane proteins in soluble, well-folded conformations (Cappuccio et al, 2008;Kubick, Gerrits, Merk, Stiege, & Erdmann, 2009;Liguori, Marques, & Lenormand, 2008;Matthies et al, 2011;Sachse, Dondapati, Fenz, Schmidt, & Kubick, 2014;Schwarz et al, 2007). Additionally, detergents such as N-dodecyl-β-D-maltoside (DDM) and Triton X-100 are also commonly used as additives to prevent aggregation of hydrophobic polypeptide sequences (Jaffee & Imperiali, 2013;Klammt et al, 2004;Lyukmanova et al, 2012;Seddon, Curnow, & Booth, 2004). Given the emergence of efforts to synthesize membrane proteins with CFPS, we aimed to develop an Escherichia coli crude extract-based platform that combines CFPS and IVG for synthesis and characterization of OSTs (Figure 1).…”
Section: Introductionmentioning
confidence: 99%